SEVASTOPOL IN GUIDEBOOKS OF THE NINETEENTH AND THE TWENTIETH CENTURIES: URBAN SPACE BETWEEN MEMORY, WAR, AND THE TOURIST NARRATIVE (City: History, Culture, Society, 2026)
This study examines Sevastopol as an urban space in which military experience and narratives of heroism shaped urban identity, spatial organization, and cultural memory. The object of analysis is a corpus of guidebooks published between 1857 and 1969. The central research question addresses how the spatial traces of war—bastions, ruins, and memorial sites—combined with heroic myths, were reinterpreted within tourist and cultural narratives that ultimately formed the symbolic geography of Sevastopol.The theoretical framework draws on concepts of military urbanism (Stephen Graham; Eyal Weizman), lieux de mémoire (Pierre Nora), politics of memory (Aleida and Jan Assmann), and symbolic geography. Methodologically, the study employs content analysis, narrative and discourse analysis of textual and visual materials, as well as a comparative approach that allows for tracing continuity between imperial and Soviet narrative regimes.The comparative analysis of guidebooks and their narrative structures demonstrates a transformation in the image of Sevastopol—from a “city of ruins” and a symbol of sacrifice in the nineteenth century to a canonical “hero city” in the Soviet period. Guidebooks functioned not merely as sources of information for travelers but as instruments of ideological construction of urban space, where memory, myth, and tourism were closely intertwined. The study highlights the role of cultural texts in shaping memory politics and in producing the symbolic space of urban landscapes.
Keywords: Sevastopol, guidebooks, military urbanism, politics of memory, symbolic geography, urban narratives